1990
DOI: 10.1002/1097-0142(19901015)66:8<1692::aid-cncr2820660807>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced squamous cell carcinoma of the skin with cisplatin, 5-fluorouracil, and bleomycin

Abstract: The authors treated 14 patients with advanced squamous cell carcinoma (SCC) of the skin or lip with one to four cycles of combination chemotherapy consisting of cisplatin by bolus injection, and 5-fluorouracil (5-FU) and bleomycin by continuous 5-day infusion. Objective responses were seen in 11 of the 13 evaluable patients (84%). Four patients had a complete remission (30%) and seven patients, a partial remission (54%). Local control after definitive complementary radiation and/or surgical treatment was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(134 citation statements)
references
References 6 publications
(1 reference statement)
0
130
0
Order By: Relevance
“…Experimental trial of cisplatin in combination with bleomycin and 5-fluorouracil to produce tumor regression permitting surgery has been reported in 11 patients. 82 Results from randomized trials comparing chemotherapy vs adjuvant RT alone in high-risk cSCC are awaited. Further prospective clinical trials are also required to clarify the role of chemotherapy in highrisk cSCC.…”
Section: Chemotherapymentioning
confidence: 99%
“…Experimental trial of cisplatin in combination with bleomycin and 5-fluorouracil to produce tumor regression permitting surgery has been reported in 11 patients. 82 Results from randomized trials comparing chemotherapy vs adjuvant RT alone in high-risk cSCC are awaited. Further prospective clinical trials are also required to clarify the role of chemotherapy in highrisk cSCC.…”
Section: Chemotherapymentioning
confidence: 99%
“…[654][655][656][657][658] These were generally small case series with only a small number of patients with eligible SCCs, or case reports, and are summarised in Table 57. In all of the studies definitive initial treatment with surgery or radiotherapy was not possible.…”
Section: Combination Systemic Treatmentsmentioning
confidence: 99%
“…655 Of three patients with SCCs of disfiguring size who were treated with neoadjuvant chemotherapy prior to surgery, complete response was seen in two patients, although one of them had a local recurrence of tumour after 8 months, and no response was seen in one patient who died from their disease 10 months after treatment. 656 No recurrences or metastasis were reported in the remaining studies, although these were all single case reports. 654,657,658 All of the studies reported adverse events related to chemotherapy.…”
Section: Combination Systemic Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadek et al reported on the treatment of 14 patients with advanced squamous cell carcinoma of the skin or lip with a combination of bolus cisplatin, plus a five-day infusion of bleomycin and 5-fluorouracil. (Sadek, Azli et al 1990) Four complete and seven partial responses were observed and in seven patients, tumor regression permitted subsequent definitive local treatment with either surgery or radiation therapy.…”
Section: Systemic Therapy For Advanced Sccsmentioning
confidence: 99%